Journal of Environmental Radioactivity - Journal of Environmental Radioactivity (Elsevier, 2026)
Provides an international, peer-reviewed forum for the publication of original research and review papers on all aspects of radioactivity in natural systems. The journal focuses on the occurrence, behavior, transfer, and distribution of environmental radionuclides, including experimental and theoretical studies, as well as predictive modeling. It also addresses radioecological and radiological effects, environmental monitoring, and the use of radionuclides as tracers in natural processes.
FI 0.38
Q3
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Radiactividad ambiental; Sistemas naturales; Radionúclidos ambientales